2020
DOI: 10.21512/jas.v8i1.6435
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral Growth and Income Inequality in ASEAN-5 Countries: Case of Low-Middle Income Economies

Abstract: This paper aims to explore the relationship between growth in economic sectors, especially manufacturing, service, and agriculture, towards income inequality. Furthermore, it utilizes panel data for low-middle income ASEAN countries. The result shows that the share of agricultural sector in GDP has a significant and negative relationship with income inequality. In fact, the effect is robust for the incorporation of control variables. Therefore, it underlines the importance of agricultural sector development fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Our results support past literature on the positive drivers of reducing income inequality that include economic globalization, fiscal capacity, agricultural sector growth, and per capita income (Bergh & Nilsson, 2010; Chen et al, 2016; Goñi et al, 2008; González Gordón & Resosudarmo, 2019; Ha et al, 2019; Raeskyesa, 2020). Ha et al (2019) found that an increase in per capita GDP reduces income inequality in Vietnam.…”
Section: Critical Discussion Of Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results support past literature on the positive drivers of reducing income inequality that include economic globalization, fiscal capacity, agricultural sector growth, and per capita income (Bergh & Nilsson, 2010; Chen et al, 2016; Goñi et al, 2008; González Gordón & Resosudarmo, 2019; Ha et al, 2019; Raeskyesa, 2020). Ha et al (2019) found that an increase in per capita GDP reduces income inequality in Vietnam.…”
Section: Critical Discussion Of Resultssupporting
confidence: 90%
“…While the declining share of agriculture in GDP shows a negative impact on income inequality, the results also reveal that agricultural growth has been more inclusive than the other sectors. Similarly, Raeskyesa (2020) examines the effects of sectoral growth on income inequality in the Association of Southeast Asian Nations (ASEAN) countries. They found that a rise in the share of agricultural GDP reduces income inequality, mostly by increasing shares of forestry and fishing activities.…”
Section: Linkage Between Income Inequality and Sectoral Growthmentioning
confidence: 99%
“…The expansion of hotel, restaurant, and agriculture cash crops requires land access to expand their economies. These findings should be taken into account as Indonesia has still sustained cash crops (e.g., coffee, cacao, and oil palm) as a significant economic export contribution (Neilson, Pritchard, Fold, & Dwiartama, 2018), and the agricultural sector is found to be significant to reduce the country's inequality (González-Gordon, Resosudarmo, 2019;Raeskyesa, 2020). Thus, this study underscores the prudent and holistic perspectives of observing the tourism sector and other economic sectors in Indonesia.…”
Section: Abstrakmentioning
confidence: 65%
“…One could assume that the tradeoff happens due to the factors of production competition, as the agriculture and tourism sector (hotels and restaurants) requires land for its activities. However, agricultural productivity improvement is still vital for the overall Indonesian economy, as it shows through the input-output analysis that the agriculture sector's output is an essential input for the tourism sector, and the agricultural sector is effective in reducing the country's inequality (González-Gordon et al 2019;Raeskyesa, 2020). In this context, it may be beneficial to consider Agri-Food tourism (Liu, Yen, Tsai, & Lo, 2017) and nature tourism (Allen, 2015).…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…This economic inequality has prevailed in the Indonesian economy (Hasudungan & Raeskyesa, 2021). Despite the significant economic growth, the regional convergence debates in Indonesia have been a vivid discussion among national and even global economists (Raeskyesa, 2020). With these heightening concerns, the paper aims to investigate the existence of regional convergence and determine factors of regional economic growth in Indonesia.…”
Section: Introductionmentioning
confidence: 99%